Mapping And Economic Potential Assesment Of Medicinal Plants in Sumber Agung Village, Wan Abdul Rahmanpublic Forest Park, Betung Mountain Lampung - Lande, Martha L.; Umar, Suratman (Proceeding International Conference on Global Resource Conservation, 2013)
Wan Abdul Rahman Public Forest Park (TAHURA) is a forest reserve in Lampung that shelter various and important biodiversity in particular medicinal plants. However, because of illegal activities and land functions change into plantations the biodiversity contained in the forest park are suffered from disturbances and threats. Before the threats are continuing ruin the park we conducted mapping and assessing the economic potential of medicinal plants therein. It is hoped that our study results can be used as a consideration and data based for designing policy to stop the destruction and other illegal activities in the precious forest park. The aim of this study is to reveal the diversity and abundance of medicinal plants and mapping the distribution of those medicinal plants. The research has been successfully conducted from June until October 2008 by surveying Â Sumber Agung village area and conducting vegetation analysis by using quadrat method. Based on the results we concluded that in Sumber AgungÂ village was found 55 medicinal plant species that exist in the form of tree shrub and herb. Most of those 55 medicinal plants species are distributed irregularly. Based on the economic assessment there was found that the economic value the medicinal plants in the rank of Rp. 95.738 per hectare until Rp. 4.505.236 per hectare.Â Keywords: Betung Mountain, Medicinal plants, mapping